POTENSI KOMPOSIT OKSIDA LOGAM-KITOSAN SEBAGAI AGEN ANTIDIARE - Siska Musiam; Eka Kumalasari (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Diarrhea is a defecation disorder characterized by defecating more than three times a day with a liquid stool consistencBABy, which may be accompanied by blood and/or mucus. Infection is still the main cause of diarrhea. The large number of cases of diarrhea due to infection means that antibiotics are still widely used in treating diarrhea. Irrational use of antibiotics can result in the emergence of side effects and resistance. To prevent this, diarrhea treatment can use materials that are able to absorb toxins and bacteria in the digestive tract, and are safe for the human body. Chitosan is an environmentally friendly material that has a large network of pores. Some metal oxides have been found to have good chemical affinity. The metal oxide-chitosan composite in nano size is predicted to allow the absorption of toxins and bacteria, but is easily released again by the body. In this research, metal oxide (Fe)-chitosan composite material was synthesized using 2 methods designed to have an antidiarrheal effect. The antidiarrheal effect is observed by its ability to absorb liquids containing natural ingredients. The results of this research showed that the composite material synthesized using a liquid reaction (13,861 ppm to 11,082 ppm) produced a stronger adsorption capacity compared to the composite material synthesized using a solid reaction (13,861 ppm to 11,265 ppm).